BIDAN DI ERA UU RI NO 17 TAHUN 2023 - Putri Wardhani; Siti Nur Umariyah Febriyanti; Sutrisno; Widya Kusuma Ningsih (Universitas Karya Husada Semarang, 2024)
The increasing public health status in Indonesia cannot be separated from the role of competent health workers Healthworkers are the government's extended arm to oversee a healthy community in accordance with the National Medium-Term Development Plan 2014-2019. Maternity care is an integral part of health care, aimed at realizing family welfare in order to achieve a quality family. Undang-Undang No 17 of 2023 concerning health, which is the latest, contains several new rules for health workers. In this law, midwives are referred to as healthcare workers With the issuance of this latest law, health services in Indonesia will automatically refer to this law, and several previous laws will become invalid or adjusted The issue to be examined is, what is the role of midwives in this latest health law era? The method used is qualitative descriptive, observation by conducting open interviews with a list of questions, comparing the results in the field with government regulations related to midwifery services The analysis used is narrative analysis built inductively from general to specific. The regulation related to healthcare workers, especially midwives, has not been specifically regulated in this law Midwives are categorized as healthcare workers who carry out health efforts in accordance with their authority A significant change in this latest law is the implementation of a lifelong professional license (STR) which previously only applied every 5 years and must be extended. This is what makes the pros and cons among professional organizations considering the science that must always be updated.